An index of student learning enthusiasm based on digital learning empowerment during the Covid-19 in Gondangmanis Village - Zulfikar Zulfikar; Amilia Zakiyatuz Zahro; Izzatul Abidah (Universitas Muhammadiyah Magelang, 2022)
During the Covid-19 period, digital learning is the last option, and it is causing concern among parents about the possibility of student learning returning to normal. According to the findings of the community survey, parents faced numerous challenges, as evidenced by students' decreased enthusiasm for learning. Based on the existing issues, community service activities in the Gondangmanis village are required, as well as intensive assistance in developing student interest through online learning empowerment. According to the results of the student ability assessment, 90% of the students are in the